Improving Students' Speaking Ability using Podcast - Bella, Clara Claudea Oxza (Universitas Negeri Surabaya, 2022)
This study aims to see improvements in students' speaking ability after using podcasts as a learning media. Moreover, it tends to know the implementation of podcast for teaching speaking and students’ responses toward the implementation. The study used quantitative method to identify the students’ speaking improvement with a pre-experimental design of one group pre-test and post-test and qualitative method to examine the implementation and students’ responses. The subjects were 11th-grade students of senior high school in Indonesia. In addition, the data collection was using tests, observation, questionnaire and an interview with two students who achieved the highest and lowest post-test scores. Based on a statistical analysis of pre-test and post-test scores and the questionnaire results, it showed an increase in students' speaking ability after the use of podcasts. In fact, nine students (36%) felt that their speaking ability improved highly after using podcasts, and most of the students (64%) felt their speaking' ability improved at the intermediate level. The interview results showed that students felt that the use of podcasts was more fun than the conventional method use in the class. It was also helpful in improving the students’ pronunciation of words, adding new vocabulary, and improving students' English grammar. The advantage of using podcasts was time flexibility, while the disadvantage relates to the complexity of creating and uploading podcasts.